Mathematics for elementary teachers : - Bennett, Albert B. (McGraw-Hill Higher Education, 2007)
This book is designed for a mathematics for elementary school teachers course where instructors choose to focus on and/or take an activities approach to learning. It provides inductive activities for prospective elementary school teachers and incorporates the use of physical models, manipulatives, and visual images to develop concepts and encourage higher-level thinking